A Review on Social Media as a New Venue for Promoting Culinary Destinations - Liang Mengjia; Ainul Zakiah Binti Abu Bakar; Farah Adibah Binti Che Ishak; Shahrim Ab Karim (Universitas Pendidikan Indonesia, 2023)
Food has become an important tool for destinations to attract tourists to visit them. Food tourism has become one of the most important segments within the travel market. With the development of online information technology, social media platforms are playing an increasingly important role in tourism promotion and digital marketing. This paper reviews a selection of literature on the use of social media platforms by destinations to shape destination images and promote food tourism. It was found that with the rise in the number of social media users, social media has become a new venue for food tourism promotion. But there is still a lack of systematic research generalization and theoretical guidance on how social media platforms can shape positive food destination impressions.